Mike Meyers' CompTIA Security+ Certification Passport (Exam SY0-601) - Dunkerley, Dawn; Meyers, Mike 1961- (McGraw-Hill Education, 2021)
Inside this study guide, you'll find practice questions and content review, exam tips, updated information on real-world cyberattacks, and enhanced coverage of emerging topics.
Includes index
Keywords: Computer security -- Study guides -- Examinations; Computer networks -- Study guides -- Security measures -- Examinations; Computer technicians -- Study guides -- Certification; Electronic data processing personnel -- Study guides -- Certification; Sécurité informatique; Examens; Guides de l'étudiant; Réseaux d'ordinateurs; Sécurité; Mesures; Examens; Guides de l'étudiant; Computer networks; Security measures; Examinations; Computer security; Examinations; Computer technicians; Certification; Electronic data processing personnel; Certification; Study guides